2022
DOI: 10.3389/fimmu.2022.973968
|View full text |Cite
|
Sign up to set email alerts
|

The number of donor HLA-derived T cell epitopes available for indirect antigen presentation determines the risk for vascular rejection after kidney transplantation

Abstract: The role of the indirect T-cell recognition pathway of allorecognition in acute T cell-mediated rejection (aTCMR) is not well defined. The amount of theoretical T-cell epitopes available for indirect allorecognition can be quantified for donor-recipient combinations by the Predicted Indirectly ReCognizable HLA Epitopes algorithm (PIRCHE-II). The PIRCHE-II score was calculated for 688 donor kidney-recipient combinations and associated with the incidence of first-time diagnosed cases of TCMR. A diagnosis of TCMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…These results showed that DSH is mediated primarily by the loss of alloreactive CD4 + T cells and, as such, are in accordance with experimental animal studies, which indicate a pivotal role of CD4 + T cells in allograft rejection ( 81 83 ). Moreover, recent studies have shown that a load of peptides that can be presented indirectly by the recipient HLA class II molecules (PIRCHE score) correlates with the risk for TCMR ( 84 , 85 ). These data suggest that the indirect pathway involving CD4 + T cells may be more important in TCMR than previously believed.…”
Section: Donor-specific Hyporesponsiveness After Kidney Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…These results showed that DSH is mediated primarily by the loss of alloreactive CD4 + T cells and, as such, are in accordance with experimental animal studies, which indicate a pivotal role of CD4 + T cells in allograft rejection ( 81 83 ). Moreover, recent studies have shown that a load of peptides that can be presented indirectly by the recipient HLA class II molecules (PIRCHE score) correlates with the risk for TCMR ( 84 , 85 ). These data suggest that the indirect pathway involving CD4 + T cells may be more important in TCMR than previously believed.…”
Section: Donor-specific Hyporesponsiveness After Kidney Transplantationmentioning
confidence: 99%
“…Studies on graft survival have shown that tacrolimus trough levels below 5 ug/L are associated with decreased graft survival ( 19 ). However, this relationship between tacrolimus trough levels and graft survival is also dependent on HLA epitope mismatch load, as both are associated with the risk of TCMR and ABMR ( 84 , 85 , 130 ). It is important to realize that, even with adequate trough levels of tacrolimus (between 6 and 7 ug/ml), chronic antibody-mediated rejection cannot be fully prevented ( 131 ).…”
Section: The Intensity Of Maintenance Immune Suppression Regimens—bal...mentioning
confidence: 99%